Implementasi Program Badan Penyelenggara Jaminan Sosial (BPJS) Siap Membantu dalam Mengatasi Pengaduan Masyarakat - Marpaung, Bryan Rogati Timotius; Tukiman, Tukiman (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Public services in the government bureaucracy are an indicator of a country's progress. One concrete form of public service is health service, because good health service will improve the welfare of the people in a country. The BPJS SATU (BPJS Ready to Help) program is one of the innovations carried out by BPJS Health to make it easier for participants to get community complaint services at hospitals. In its implementation, the problems related to BPJS services are that there are still many people who do not know the health insurance procedures for health facilities, then there are still concerns from hospitals that BPJS will not pay patient arrears, and there are doubts about the security of the BPJS participant data system. So this research aims to examine further the implementation of BPJS SATU (Ready to Help) services in dealing with public complaints at Dr Soetomo Hospital, Surabaya City. The research method used in this research is a descriptive qualitative method with the focus of the research here being based on indicators of success in implementing the Edward III program, including communication, resources, disposition and bureaucratic structure. The results of research on communication focus show that communication has been created that creates inclusive services and focuses on achieving the goals of program implementation. The resource focus shows that this program has quality human resources and a supporting system within it. The disposition focus shows that BPJS Health is strongly committed to improving the quality of complaint handling in the BPJS SATU program. The focus on organizational structure has been running well as evidenced by the available procedures that can be carried out by participants and implementing officers.